(untitled) (Journal of Hama University, 2024)
Aim of the study : Evaluation of the effectiveness of both Propolis and Aloevera in eliminating Enterococcus faecalis germs prevalent in the root canals of extracted teeth and comparison of its anti-infective efficacy with calcium hydroxide . Materials and methods : single root canal teeth were used . the teeth were prepared with manual and rotary files then sterilized by autoclave after that, they were infected with bacterial suspension (E.faecalis) and were incubated for 24 hours . The teeth were divided into 4 groups (n1=n2=n3=n4=15) according to the type of root canal dressing . primary bacterial samples a (befor dressing) were taken from root canals by sterile file after disposal of bacterial suspension . the b (after dressing) samples were taken in the same way where the dressings were applied for 4 days . the samples (a and b) were transported to sterile Eppendorf tubes containing 1 mm sterile distilled water then after making the dilutings then were transferred to mueller hinton agar plates and were incubated for 24 hours . Colony forming units (CFU) were counted and bacterial reduction between a and b was analyzed for all groups and then compared . Results : It has been used One Way ANOVA Test for variable of the percentage of reduction in bacterial count% in research groups , and Post Hoc Tests that associated with One Way ANOVA Test for variable of the percentage of reduction in bacterial count% to study the effect of the materials used in the study on this variable in research groups . None of these dressings was able to completely eliminate the bacterial presence in canals . Calcium hydroxide had a bacterial reduction average (89.87%) , Propolis had (23.24%) , Aloe vera had (60.5%) , whereas distilled water had (13.43%) . Conclusion : Calcium hydroxide is superior to both propolis and aloe vera in the eradication of Enterococcus faecalis by applying them for 4 days